2018
DOI: 10.3892/mmr.2018.9459
|View full text |Cite
|
Sign up to set email alerts
|

Theanine, an antitumor promoter, induces apoptosis of tumor cells via the mitochondrial pathway

Abstract: Theanine, an active component of green tea (Camellia sinensis), is considered a modulator of chemotherapy. To further investigate the anticancer activity of theanine, the present study investigated the cytotoxic effect of theanine at the concentration of 600 µg/ml, in the human HepG2 hepatoblastoma and HeLa adenocarcinoma cell lines, in comparison with the normal L02, H9c2 and HEK293 cell lines using a MTT assay. It was found that theanine induced cell death in the tumor cells, but not in the normal cells. Not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 24 publications
0
19
0
Order By: Relevance
“…Four in vitro studies confirmed apoptotic effects of theanine on the liver cancer HepG2 (Xin et al, 2018), hepatocellular carcinoma SMMC7721 (G. Zhang et al, 2016), Lewis lung cancer (LLC) (Ji et al, 2014), and cervical HeLa (J. Liu et al, 2016) cells.…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations
“…Four in vitro studies confirmed apoptotic effects of theanine on the liver cancer HepG2 (Xin et al, 2018), hepatocellular carcinoma SMMC7721 (G. Zhang et al, 2016), Lewis lung cancer (LLC) (Ji et al, 2014), and cervical HeLa (J. Liu et al, 2016) cells.…”
Section: Discussionmentioning
confidence: 85%
“…The main characteristics and results of the included studies are summarized in Tables 2 and 3. Of the 14 included articles, three were in vitro (Ayoub & Melzig, 2006; Friedman et al, 2007; Xin et al, 2018), four were in vivo (Fujii & Inai, 2008; Shojaei‐Zarghani, Khosroushahi, & Rafraf, 2020a; Sugiyama & Sadzuka, 1998; W.‐J. Zeng et al, 2018; G. Zhang et al, 2002), and seven were designed by a different combination of in vitro, ex vivo, and in vivo methods (Fan et al, 2020; Ji et al, 2014; J. Liu et al, 2016; Q. Liu et al, 2009; G. Zhang et al, 2016; G. Zhang et al, 2001; Zhao et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Secondly, L-theanine could induce or inhibit the digestive system cancers. It was shown that L-theanine (600 μg/mL) could induce apoptosis of tumor cells through the mitochondrial pathway in human HepG2 hepatoblastoma cells and HeLa adenocarcinoma cells ( 71 ). Furthermore, L-theanine and its semi-synthesized derivative (R)-2-(6,8-dibromo-2-oxo-2H-chromene-3-carboxamido)-5-(ethylamino)-5-oxopentanoic ethyl ester (DTBrC) also restrained the growth and migration of human hepatocellular carcinoma (HHC) cells in in vitro , ex vivo , and in vivo HHC models, and the mechanism of this effect was that L-theanine and DTBrC blocked the Met/EGFR/vascular endothelial growth factor receptor (VEGFR)-Akt/NF-κB pathways ( 72 ).…”
Section: Health Benefits Of L-theaninementioning
confidence: 99%